Analisis Program Pelatihan Bahasa Inggris Sebagai Strategi Komunikasi Antarbudaya Pada Perusahaan Multinasional - Yustika, Wida; Aisyah, Siti (STAI Darul Kamal NW Kembang Kerang, 2025)
International business involves interactions between countries in various forms, such as foreign direct investment and multinational corporations, which face communication challenges due to cultural differences. Expatriate workers, in particular, must adapt to new environments and communicate effectively with individuals from different cultural backgrounds. Mastery of English is an absolute requirement for employees in multinational companies, as this language serves as a communication tool and determinant of competitiveness in the global market. This study aims to explore the role of English language training in improving intercultural communication skills in multinational companies. Using a literature review methodology, this study analyzed academic journals and relevant sources published in the last ten years to assess the effectiveness of English language training programs. The results show that effective training not only improves linguistic proficiency, but also fosters cultural awareness and sensitivity. The contribution of this study lies in a deeper understanding of the relationship between language training and intercultural communication, as well as implementation strategies that can be applied to improve communication effectiveness in multinational companies.